The Utilization of @buiramira’s Educational TikTok Content on the Use of Academic Information Sources among Library and Information Science Students - Diva Oktavia; Rini Asmara (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
The rapid advancement of digital technology has transformed how academic information is accessed and used, particularly through social media platforms such as TikTok, which increasingly serve as alternative learning resources. However, the use of social media as an academic information source raises important questions about its effectiveness and contribution to students’ information behavior. This study aims to analyze the utilization of @buiramira’s educational TikTok content in relation to the use of academic information sources among students of the Library and Information Science Program at Universitas Negeri Padang. A quantitative approach with a descriptive research design was employed, involving 64 respondents selected through proportionate stratified random sampling. Data were collected using questionnaires and analyzed through descriptive statistics, Pearson correlation, and simple linear regression. The findings indicate that the utilization of @buiramira’s educational TikTok content was categorized as high, with perceived usefulness and perceived ease of use scores of 3.08 and 3.07, respectively. The use of academic information sources was also categorized as high, as reflected in information behavior (3.13), information-seeking behavior (2.85), information-searching behavior (2.96), and information-use behavior (3.01). Pearson correlation analysis revealed a strong and significant positive relationship between the utilization of educational TikTok content and the use of academic information sources, with a correlation coefficient of 0.656 and a significance level below 0.001. Simple linear regression further demonstrated a significant effect, with an F-value of 46.888. The study concludes that educational TikTok content can function as an initial academic information source and a supporting medium for students’ academic activities. These findings contribute to the literature on digital information behavior and highlight the need to strengthen students’ information literacy skills so that they can critically evaluate the credibility, relevance, and depth of academic information obtained through social media.